Intellectuality and Artistic Aspect of Author in the Concept of Spinoza's Rationalism (Expressive-Typography on Indonesian New-Age Poem) - Achmad Naufal Irsyadi; Althafurrahman Althafurrahman; Nala Maziya Fitriyah (Institut Agama Islam Negeri (IAIN) Manado, 2022)
Intellectuality and Artistic Aspect of Author in the Concept of Spinoza's Rationalism(Expressive-Typography on Indonesian New-Age Poem). Typography is a rarecourse in the study of literature. Sometimes, it is neglected. In this study, webelieved that all parts of literary work contained valuable marks that could benefithumans and the development of literary studies. Most studies commonly focusedon how an author used figurative language in his work, not typography. In thisstudy, we investigated and observed in nature intellectuality and aestheticpreference of Wiji Thukul in the construction of expressive poems on his own. Weused Spinoza's rationalism as an approach for this purpose. In our analysis, wefound that being a member of the democratic party contributed to thedevelopment of Wiji Thukul's intellectuality so that he could become more literateabout social reality, while the experience of being a poet, in any event, hadcontributed to his competence and aesthetic preference. In this essence, webelieved that substance, value, and ideology are the most prominent in the currentliterary work's content, as well as in its form.Keywords: Literary studies, intellectuality, Aesthetic, Spinoza, typography